SCIENTIFIC AND THEORETICAL BASIS OF INVESTMENTS IN FIXED CAPITAL - Khoshimov Sabir Murtazaevich (American Journals, 2025)
The article attempts to reveal the economic essence of the concept of investment in fixed capital, its various aspects from capital investments, based on the theoretical views and approaches of various economists. In addition, the importance of investment in fixed capital in the development of the country's economy, legal basis, conclusions and recommendations are considered.
Keywords: Investments, capital investments, fixed capital, financial investments, non-financial investments, physical capital, human capital, intangible assets.